Pertumbuhan dan Perkembangan Jaringan Meristem Bawang Merah (Allium ascalonicum L.) Kultivar Katumi Secara In Vitro - Lamro Purba; Erni Suminar; Denny Sobardini; Wieny Rizky; Syariful Mubarok (Jurnal Agro, 2017)
This study aimed for knowing and obtaining the best concentration of kinetin and NAA interaction effects in influencing the shoot induction, knowing how the plant growth regulators in induction mediastill affect the shoot additionin the MS0media and also knowing the largest number of roots in rooting media for shallot by in vitro. The experiment was conducted at Laboratory of Tissue Culture Seed Technology, Faculty of Agriculture, Padjadjaran University, during January 2011 until May 2011. This experiment divided in 3 stages, namely shoot induction stage, shoot subculture to MS0 media stage and shoot subculture to rooting media stage. Experimental method used in the shoot induction stage was factorial Completely Randomized Design with three replications. The first factor was the kinetin with four levels,0, 1, 2, and 3 mg L-1. The second factor was the NAA with three levels, as 0, 0.01, and 0.1 mg L-1. Basic media used for each treatment was MS. The experiment result showed there was an interaction between kinetin and NAA on shoot induction stagewith the plantlet height, leaf number, and shoot addition. The best result for leaf number was gained from interaction with 2 mg L-1 kinetin without NAA,while the treatment of 2 mg L-1 kinetin with 0.01 mg L-1 NAA gave a better interaction for theshoot addition variable.